(untitled) - William A. Haviland (Belmont, CA, 2008)
Explore the most fascinating, creative, dangerous, and complex species alive today: you and your neighbors in the global village. With compelling photos, engaging examples, and select studies by anthropologists in far-flung places, the authors of ANTHROPOLOGY: The Human Challenge provide a holistic view of anthropology to help you make sense of today's world. With this text you will discover the different ways humans face the challenge of existence, the connection between biology and culture in the shaping of human behavior, and the impact of globalization on peoples and cultures around the world
Keywords: Anthropology